Contemporary theatre, film and television. a biographical guide featuring performers, directors, writers, producers, designers, managers, choreographers, technicians, composers, executives, dancers, and critics in the United States, Canada, Great Britain and the world - Riggs, Thomas 1963- (Gale virtual reference library, 2012)
Biographical reference providing information on individuals active in the theatre, film, and television industries. Covers not only performers, directors, writers, and producers, but also behind-the-scenes specialists such as designers, managers, choreographers, technicians, composers, executives, dancers, and critics from the United States, Canada, Great Britain, and the world.